Comparative pathogenicity of H5N6 subtype highly pathogenic avian influenza viruses in chicken, Pekin duck and Muscovy duck. Issue 3 (27th February 2019) - Uchida, Yuko; Mine, Junki; Takemae, Nobuhiro; Tanikawa, Taichiro; Tsunekuni, Ryota; Saito, Takehiko
Summary: In Japan during the 2016–2017 winter season, clade 2.3.4.4 highly pathogenic avian influenza viruses (HPAIVs) of the H5N6 subtype caused 12 outbreaks in chicken and Muscovy duck farms. These viruses have been circulating in Vietnam and China since 2014. In this study, we evaluated the susceptibility of chicken, Pekin duck ( Anas platyrhynchos domesticus ) and Muscovy duck ( Cairina moschata ) to H5N6 HPAIVs that originated in Japan, Vietnam and China. The H5N6 HPAIVs examined in this study were highly lethal to chickens compared with their pathogenicity in Pekin duck and Muscovy duck. One of five chickens infected with A/Muscovy duck/Aomori/1‐3T/2016 (MusDk/Aomori) survived despite viral shedding, although all of the chickens infected with the other viruses died. The 50% chicken lethal dose differed among the Japanese strains that shared the same gene constellation indicating that gene constellation was not a major determinant of pathogenicity in chicken. MusDk/Aomori, A/chicken/Niigata/1‐1T/2016 (Ck/Niigata) and A/duck/Hyogo/1/2016 (Dk/Hyogo) infected all Muscovy ducks inoculated; Ck/Niigata killed 50% of the ducks it infected whereas the other two did not kill any ducks. A/chicken/Japan/AnimalQuarantine‐HE144/2016 (HE144) isolated from chicken meat that originated in China was highly pathogenic to Pekin duck: all of the ducks died within 3.75 days of inoculation. This study shows that the pathogenicity of the clade 2.3.4.4 H5N6 HPAIVs differs not only between hosts but also within the same host species.